PELATIHAN DAN PENDAMPINGAN GURU SEKOLAH DASAR DALAM MENYUSUN MEDIA INOVATIF BERBASIS SCREENCAST O MATIC DI MASA PENDEMI COVID-19 - Eko Febri Syahputra Siregar; Suci Perwita Sari; Ismail Saleh Nasution (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
This Community Partnership Program is "Training and Assistance of Elementary School Teachers in Willingness to Innovative Media Based on Screencast-O-Matic in the Covid-19 Pandemic". This program aims to assist teachers in developing innovative learning media based on Screencast-O.Matic that can increase students' interest and motivation in learning during learning during the Covid-19 pandemic. The reason for choosing MI Al-Fajar Sei Mencharim as a partner is to improve the quality of learning at the school. Another reason is that this school rarely receives training that supports job professionalism. The methods used in this PKM activity are 1) preparation, namely an initial visit to agree on a time for the implementation of the activity; 2) implementation. namely the implementation of training activities in preparing innovative learning media based on Screencast-O-Matic, as well as; 3) evaluation, namely collecting learning media that have been completed by the participants for feedback. This activity can be said to be successful, this is because of the 10 activity participants, 8 teachers were able to produce Screencast-O-Matic-based learning media by recording their teaching materials through this application, while the other two participants had problems with their laptops.